Efficacy and safety of the integrated puncture method vs. the conventional puncture method in Peripherally Inserted Central Catheter placement for cancer patients - Wang, Xinpeng; Yang, Yong; Zheng, Yuanyuan; Chen, Jie; Shen, Yanfen (Frontiers in Surgery, 2025)
ObjectiveThis study aims to assess the efficacy and safety of the integrated puncture method compared to the conventional puncture method in cancer patients undergoing PICC placement.MethodsThe retrospective analysis included 224 cancer patients who underwent PICC placement at the vascular access center of Beijing cancer hospital from March 2023 to September 2023, with 111 patients in the integrated puncture method group and 114 patients in the conventional puncture method group.ResultsThe integrated puncture method group demonstrated a significantly higher one-needle puncture success compared to the conventional puncture method group (P = .01). Additionally, the group exhibited notably lower rates of blood-borne exposure and post-operative subcutaneous congestion (P < .001, P = .04). The integrated puncture method group also led to significantly shorter durations for tourniquet application, puncture time, and overall catheterization time compared to the conventional puncture method group (All P < .001). No statistically significant differences were observed between the two groups regarding post-operative complications such as dermatitis, catheter-related infection, catheter blockage, and catheter-related thrombosis (P > 0.05).ConclusionThe integrated puncture method for PICC placement enhances one-time puncture success rates, improves catheterization efficiency, and reduces the risks of blood-borne exposure and subcutaneous congestion.